Prepoznava, obravnava in preprečevanje bolečine pri novorojenčkih in dojenčkih - Javh, Tanja (Medicinski razgledi, 2003)
Pain assessment and evaluation in neonates and infants remains a significant problem. Pain management and prevention in this age group is less than optimal. Nonpharmacologic and pharmacologic interventions for relief of pain during minor invasive procedures are infrequently employed. Recent research evidence has shown the efficacy of sugar solutions and topical anaesthetics for relief of procedural pain. The employement of neonatal pain assessment tools that are easily aplicable in clinical settings would provide more objective evaluation of pain response, the development of pain management careplans, and the effectiveness of pain relief interventions. The objectives of this study were to assess the applicability of Neonatal Infant Pain Scale (NIPS) in clinical settings and evaluate effective and safe interventions thatrelieve pain in neonates and infants. Hypotheses:1. NIPS is applicable in the clinical settings. 2. Oral glucose solution is effective in reducing pain-related behavior in neonates and infants undergoing minor invasive procedures. 3. Application of a topical anaesthetic is effective in reducing pain-related behavior in neonates and infants undergoing minor invasive procedure. 60 neonates and infants undergoing venepuncture and intravenous catheter insertion randomly assigned to one of three treatment groups: (1) no treatment, (2) oral glucose solution, (3) topical anaesthetic. Statistical analysis: internal consistency of NIPS was established by Cronbach's alphas; interrater reliability of NIPS was established by Pearson's correlations, concurrent validity was established by correlations with heart rate. Differences between group median pain scores were established by analyses of variance. Internal consistency was high: Cronbach's alphas ranged from 0,87 to0,91. Interrater reliability was high: Pearson's correlations ranged from 0,86 to 0,94. (Abstract truncated at 2000 characters).
Keywords: Anestetiki lokalni; Pain; Bolečina; Diagnosis; Bolečina, merjenje; Drug Therapy; Glukoza; Prevention And Control; Pain Measurement; baby; Dojenček; Glucose; Novorojenček; Therapeutic Use; preprečevanje; dojenčki; Anesthetics, Local; Infant, Newborn; Infant; diagnostika